MENINGKATKAN PENGETAHUAN IBU TENTANG TANDA – TANDA DEHIDRASI DAN PENANGANANNYA PADA ANAK DIARE MELALUI PENDIDIKAN KESEHATAN MENGGUNAKAN LEAFLET - Desak Putu Kristian Purnamiasih (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Diarrhea is an endemic disease that has the potential to cause Extraordinary Events (KLB) and is still a contributor to mortality in Indonesia, especially in children under five. Diarrhea that is not treated quickly will have a direct result in impaired fluid and electrolyte balance. Efforts to increase mother's knowledge about diarrhea and its handling is through health education. This study uses a pre-experimental research design with a one group pre-posttest only design approach. The number of samples in this study were 20 people. The results showed that the majority of respondents (45%) were in the age range of 31-40 years, and the minority (25%) were in the age range of 41-50 years. the majority of respondents (50%) have a SMA/SMK education and the minority (5%) have a D2 education. The results of the Wilcoxon statistical test were p-value 0.000 <0.05. There is an effect of providing health education about diarrhea and signs of dehydration in children.